Successful Primary Percutaneous Coronary Intervention in a young patient in peripheral hospital and its out come. (Journal of Invasive and Clinical Cardiology, 2023)
Among all coronary artery disease (CAD) ST-T elevated MI is the most emergency condition to treat within time. but in our country all peripheral hospital has no enough scope for the recommended treatment, that is primary percutaneous coronary intervention (PCI) due to lake of infrastructure and trained cardiologist. Most of our patients does not reach to hospital within the golden time. In most of these patients are treated with pharmacological revascularization by Streptokinase or Tenecteplase. Few patients are saved who are with no other risk factors and can reach in hospital within the time frame of myocardial infarction cascade. For this consequence most of our patients suffers from the sequalae of myocardial infarction, that may be arrhythmias, cardiomyopathy to death. We performed primary PCI in peripheral hospital in a young patient successfully and the outcome is satisfactory. We want to continue this service in our hospital for preventing mortality and morbidity of our cardiac patients.J Inv Clin Cardiol 2023; 5(1): 24-28